Satureja montana essential oil, zein nanoparticles and their combination as a biocontrol strategy to reduce bacterial spot disease on tomato plants - Oliveira-Pinto, Paulo R. (2021)
Tomato bacterial spot (Bs), caused by Xanthomonas spp., including X. euvesicatoria (Xeu) remains a major threat for tomato production. The emergence of copper resistance strains of Xeu calls urgently for eco-friendly phytosanitary treatments as sustainable green alternatives for disease control. Satureja spp. essential oil (EO) has antimicrobial activity against xanthomonads and combined with zein nanoparticles (ZNPs), might offer a viable option for field applications. This study aims to evaluate the effects of S. montana EO, of ZNPs, and their combination in a nanoformulation, on Xeu quantity, and how these compounds modulate molecular and physiological changes in the pathosystem. Uninfected and infected tomato plants (var. Oxheart) were treated with EO; ZNPs and nanoformulation (EO + ZNPs). Treatments reduced Xeu amount by a minimum of 1.6-fold (EO) and a maximum of 202-fold (ZNPs) and improved plants health. Nanoformulation and ZNPs increased plants phenolic content. ZNPs significantly increased GPX activity and reduced CAT activity. Overall treatments upregulated transcripts of the phenylpropanoid pathway in infected plants, while ZNPs and nanoformulation upregulated those transcripts in uninfected plants. Both sod and aao transcripts were downregulated by treatments in infected plants. These findings demonstrate that S. montana EO, ZNPs and their nanoformulation are suitable to integrate tomato bacterial spot management strategies, mainly due to their antimicrobial activity on Xeu, however further field studies clarifying the long-term action of these products are required. These results also support the prophylactic potential of ZNPs on tomato bacterial spot.